2003
DOI: 10.1038/sj.bjc.6601218
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prognostic factors in patients in phase I trials of cytotoxic drugs vs new noncytotoxic agents

Abstract: The aims of this study were to identify prognostic variables for toxicity and survival in patients with cancer participating in phase I clinical trials and compare characteristics of those treated with cytotoxic chemotherapy (CT) and non-cytotoxic drugs (non-CT). Data were collected from 420 (114 CT, 306 non-CT) patients enrolled in 16 phase I trials (five CT and 11 non-CT trials) in one cancer centre. Analyses of all patients were used to compare treatment groups, identify predictive variables for toxicity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 18 publications
5
40
0
Order By: Relevance
“…These results were similar to our survival analysis, which showed that classical cytotoxic-based regimens resulted in longer OS compared to biological agents. This trial also confirmed that RR was significantly higher in patients receiving cytotoxic agents compared to patients who received non-cytotoxic agents (14.1 vs 1%, Po0.001) (Han et al, 2003).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These results were similar to our survival analysis, which showed that classical cytotoxic-based regimens resulted in longer OS compared to biological agents. This trial also confirmed that RR was significantly higher in patients receiving cytotoxic agents compared to patients who received non-cytotoxic agents (14.1 vs 1%, Po0.001) (Han et al, 2003).…”
Section: Discussionsupporting
confidence: 65%
“…However, one of the drawbacks of these studies has been that most analyses have been performed over a long period of time, some of them over 10 years. Moreover, most of these studies focused on the 'classical cytotoxic drug development era' and not on the newer generations of molecularly targeted or biological agents (Yamamoto et al, 1999;Han et al, 2003;Penel et al, 2008).…”
mentioning
confidence: 99%
“…The incidence was lower in patients treated with targeted therapy than in patients who received chemotherapy. These observations were similar to those of previously published reports [46,47]. Treatmentrelated mortality in phase I trials is generally low [29,30,50].…”
Section: Discussionsupporting
confidence: 91%
“…Several retrospective studies evaluated prognostic factors for survival to determine the risks for early mortality in the phase I setting [43][44][45][46][47][48]. A group from Royal Marsden Hospital in London developed a prognostic score for predicting survival, which included albumin, LDH, and number of metastatic sites, and validated it in a prospective study with 78 patients [49].…”
Section: Discussionmentioning
confidence: 99%
“…Most conventional phase I trials therefore employ strict eligibility criteria to exclude those for whom this risk-benefit balance is least favorable, including Eastern Cooperative Oncology Group (ECOG) performance status (PS) 0 to 2, acceptable visceral organ function, and a projected life expectancy of greater than 3 months. However, the clinical outcome of patients enrolled on phase I trials using these criteria remains highly variable (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), and still permits the inclusion of unsuitable patients for whom inclusion on trial is unlikely to be either in their, or the trial's, benefit. Thus, greater efforts are required to improve the screening of advanced cancer patients for phase I studies.…”
Section: Introductionmentioning
confidence: 99%